Applications of Artificial Intelligence in clinical studies: Ethical dilemmas - Sargiotis, George-Chrisovalantis (Bioethica, 2023)
The application of Artificial Intelligence in Clinical Trials raises many ethical dilemmas concerning the ensuring of subjects' data, the transparency of processes, the implications on doctor-patient relationship and the healthcare decision-making. To investigate these dilemmas, the literature on AI' applications in clinical trials was reviewed and data were collected and analyzed. It was observed that applications of AI in patients' health monitoring, in discovery of novel therapeutic approaches, in diagnostics and in chronic diseases care contributed to better or non-inferior outcomes to conventional methods. Nevertheless, different bioethical issues emerge, such as the existence of biases in algorithmic models, the inadequacy of measures for the protection of subjects' data, the incapability for attributing responsibilities in case of system or clinical errors and the weaknesses in consent procedures and regulations. The relation of Artificial Intelligence and Health in the future is promising. Therefore it is of great significance to promote further investigation on ethical dilemmas that arise from the applications of AI in clinical trials, to outline the responsibilities, obligations and rights of patients and other stakeholders that take part in clinical research.